Intelligent Radio Network Selection for Next Generation Networks - Alkhawlani, Mohammed M.; Zahary, Ammar T. (DLINE / Journal of Intelligent Computing, 2010)
In a tightly coupled Next Generation Wireless Network (NGWN), a large number of different radio access technologies (RATs) will be integrated into one common network. These RATs are owned by one operator or multicooperative operators. Selecting the most optimal and promising RAT is an important consideration for overall networks stability, resource utilization, operator benefits, user satisfaction, and Quality of Service (QoS) provisioning. However, choosing the best RAT is not a trivial task and there are many parameters and criteria to take into account when selecting the best access network. This paper presents and designs a multi criteria RNS solution that considers an environment with a co-existed WWAN, WMAN, and WLAN. The developed solution contains two modules. The first module resides in the user terminal. It contains a network-assisted terminalcontrolled algorithm to reflect the user viewpoint in the selection process. The second module resides in the CRRM entity. It contains a terminal-assisted networkcontrolled algorithm to reflect the operator viewpoint of the selection decision. The developed solution uses a combined parallel fuzzy logic control and Multi- Criteria Decision Making (MCDM) system to achievescalable, flexible, general, and adaptable solution. The simulation results show that our solution has betterand more robust performance over several reference algorithms.